Hemorojinių mazgų chirurginio gydymo rezultatų palyginimas - Denisenko, Valery Larionovich (Lietuvos chirurgija, 2010)
Valery Larionovich Denisenko 2nd Vitebsk regional clinical hospital, Nekrasova 10, Vitebsk 211000, Belarus El. paštas: boln_priem@vitebsk.by Tikslas: Palyginti prieširdžių pertvaros defekto chirurginio ir perkateterinio gydymo metodų ankstyvuosius rezultatus ir komplikacijas. Comparative analysis of chronic hemorrhoids surgical treatment Valery Larionovich Denisenko 2nd Vitebsk regional clinical hospital, Nekrasova 10, Vitebsk 211000, Belarus E-mail: boln_priem@vitebsk.by Abstract. The problem of hemorrhoids treatment has been important for more then two thousand years. After the standard closed hemmorroidectomy in the postoperative period pain syndrome long-term rehabilitation of patients, a large number of relapses, can be observed. Implementation method of rubber band ligation, as well as the trans anal doppler-guided hemorrhoidal artery ligation, are an alternative to hemorrhoidectomy in patients with hemorrhoids stage III. The analysis of treatment result was in 75 patients with chronic hemorrhoids treated at proctologic ward in the station Vitebsk (since 2008 II Vitebsk Regional Clinical Hospital) from 2002 to 2009. Accordiny to method of treatment for chronic hemorrhoids three groups of patients. Application were distinguished of trans-anal disarterization of internal hemorrhoids under doppler control with mucopexy and lifting and rubber band ligation gives positive results. In reduction of patients disability from 18,4 ± 0,5 days to 1,3 ± 0,3 days (p < 0,05) rehabilitation of the patients on faster than rehabilitation after using traditional techniques. Key words: hemorrhoids, Doppler, lifting, mucopexy.